Diseño e implementación de una aplicación móvil sobre android para la gestión remota de inventarios de hardware y software utilizando la metodología xp en la empresa (adelca) perteneciente a la provincia de pichincha, Cantón Mejía, parroquia de Aloag en el periodo de octubre a marzo del 2013 - Espín Espín, Eduardo Luis (2013)
The application mobile with the Android operating system is a support tool for the enterprise ADELCA SA, which provide staff systems department, The management remote of hardware and software inventories of each of the users to run a computer. Also the objective of mobile application development is performed using technological tools, in this case we used free software, because the code is free. Mobile devices offer more reality that provides the user of a small device that its role goes far beyond phone calls or internet surfing against other benefits. Finally the methodology that has been used for the development of the system is Extreme Programming (XP), which provides us with all life bases cycle of software development which fits any type of change that is required the mobile application during development by providing us all the bases for the construction of its various stages.